Investigation of hyperfine interactions in multiferroic oxides RMnO3 (R = Y, Dy, Tb and Ho) by means of first-principles calculations - Maciel, Levy Scalise (2025)
Multiferroic manganites, RMnO3, in both their hexagonal (space group P63cm) and orthorhombic (space group Pnma) phases, exhibit a range of technologically compelling properties such as ferroelectricity, magnetoelectric coupling, and multiferroicity. While experimental studies have revealed significant atomistic characteristics, a unified model that fully explains the microscopic origin of these properties remains elusive. In this context, hyperfine interactions provide a powerful atomic-scale probe. Parameters such as the Electric Field Gradient (EFG), its asymmetry parameter (η), and the magnetic hyperfine field (Bhf) serve as direct indicators of the local electronic and magnetic environment, offering critical insights for model development. This thesis employs first-principles calculations based on Density Functional Theory (DFT) to systematically investigate the behavior of these hyperfine parameters in RMnO3 compounds (R = Y, Dy, Ho, and Tb) across both crystalline phases. Our computational study reveals the specific structural and electronic properties that most significantly influence the hyperfine parameters in each phase. A key finding is that the standard DFT+U approach, applied solely to the manganese sites, is insufficient to accurately describe the hyperfine interactions in these compounds. This insufficiency underscores the necessity for more advanced theoretical extensions of DFT to capture the complex electronic correlations at play. Given the current scarcity of experimental hyperfine data for these systems, our results establish a foundational theoretical benchmark. This work not only provides a basis for future investigations into the microscopic mechanisms of manganites, guided by hyperfine parameters, but also identifies the precise limitations of current DFT methodologies. By delineating these limitations, we point toward new directions and necessary theoretical refinements for future research in this field.